Laboratory Aspect of Broken Heart Syndrome - Y. Kusumo Adi Arji Atmanto; Sulina Yanti Wibawa; Darmawaty E Rauf (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Broken Heart Syndrome (BHS) is the weakness of the heart muscle due to emotional stress or physical stress called cardiomyopathy. The main etiology is a sudden release of stress hormones (catecholamines), such as norepinephrine, epinephrine, and dopamine. About 90% of BHS patients are female with average age of 67-70